A moderated mediation analysis of the effect of lettering case and color temperature on trustworthiness perceptions and investment decisions. Issue 4 (2nd April 2020) - Song, Yao; Luximon, Yan; Luo, Jing
Abstract : Purpose: The purpose of this study is to test the theoretical framework of lettering case, color temperature, perceived trustworthiness and investment intentions. First, it aims to test whether the effect of lettering case on investment intentions is mediated by trustworthiness. Second, the study will examine if this process is moderated by color temperature. Design/methodology/approach: Following the behavioral research method, this study employed a 2 (the fully-lowercase slogan vs the initial-uppercase slogan) by 2 (warm-color design vs cool-color design) full factorial between-subject design. Two hundred participants were recruited for the experiment to test the hypotheses. Findings: For the lowercase slogans (vs uppercase slogans), we found that people tended to have a high level of perceived trustworthiness, which led to a high level of investment intentions. In addition, the indirect effect of the lettering case on investment intentions through the perceived trustworthiness was moderated by color temperature. Specifically, the visually warm advertisement (vs visually cool design) would strengthen the effect of lowercase slogans on customers' investment intentions. Originality/value: When people make a financial decision with limited, incomplete or overly complex information, simplified visual heuristics, rather than rational algorithmic processing, play a significant role in their decision-making process. However, only a limited amount of research has addressed the effect of the lettering case on customers' perceptions and the consequent decision-making process from a financial advertising perspective. This study tries to supplement and extend the visual heuristics theory, highlighting the role of simplified heuristics, rather than rational algorithmic processing, in financial customers' decision-making process.